A scanning probe microscopy study of nanostructured TiO2/poly(3-hexylthiophene) hybrid heterojunctions for photovoltaic applications - Letertre, Laurie; Roche, Roland; Douhéret, Olivier; Kassa, Hailu G.; Mariolle, Denis; Chevalier, Nicolas; Borowik, Łukasz; Dumas, Philippe; Grévin, Benjamin; Lazzaroni, Roberto; Leclère, Philippe (Beilstein Journal of Nanotechnology, 2018)
The nanoscale morphology of photoactive hybrid heterojunctions plays a key role in the performances of hybrid solar cells. In this work, the heterojunctions consist of a nanocolumnar TiO2 surface covalently grafted with a monolayer of poly(3-hexylthiophene) (P3HT) functionalized with carboxylic groups (–COOH). Through a joint analysis of the photovoltaic properties at the nanoscale by photoconductive-AFM (PC-AFM) and surface photovoltage imaging, we investigated the physical mechanisms taking place locally during the photovoltaic process and the correlation to the nanoscale morphology. A down-shift of the vacuum level of the TiO2 surface upon grafting was measured by Kelvin probe force microscopy (KPFM), evidencing the formation of a dipole at the TiO2/P3HT-COOH interface. Upon in situ illumination, a positive photovoltage was observed as a result of the accumulation of photogenerated holes in the P3HT layer. A positive photocurrent was recorded in PC-AFM measurements, whose spatial mapping was interpreted consistently with the corresponding KPFM analysis, offering a correlated analysis of interest from both a theoretical and material design perspective.
Keywords: hybrid heterojunctions; hybrid photovoltaic; Kelvin probe force microscopy; photoconductive-AFM; photo-KPFM; poly(3-hexylthiophene); TiO2

(untitled) - Parida, B.; Iniyan, S.; Goic, R. (Renewable Sustainable Energy Rev., 2011)

(untitled) - Polman, A.; Knight, M.; Garnett, E. C.; Ehrler, B.; Sinke, W. C. (Science, 2016)

(untitled) - Branker, K.; Pathak, M.; Pearce, J. (Renewable Sustainable Energy Rev., 2011)

(untitled) - Wright, M.; Uddin, A. (Sol. Energy Mater. Sol. Cells, 2012)

(untitled) - Mathew, S.; Yella, A.; Gao, P.; Humphry-Baker, R.; Curchod, B. F. E.; Ashari-Astani, N.; Tavernelli, I.; Rothlisberger, U.; Nazeeruddin, M. K.; Grätzel, M. (Nat. Chem., 2014)

(untitled) - Tengstedt, C.; Osikowicz, W.; Salaneck, W. R.; Parker, I. D.; Hsu, C.-H.; Fahlman, M. (Appl. Phys. Lett., 2006)

(untitled) - Chung, I.; Lee, B.; He, J.; Chang, R. P. H.; Kanatzidis, M. G. (Nature, 2012)

(untitled) - Hagfeldt, A.; Boschloo, G.; Sun, L.; Kloo, L.; Pettersson, H. (Chem. Rev., 2010)

(untitled) - Othman, M. A.; Amat, N. F.; Ahmad, B. H.; Rajan, J. (J. Phys.: Conf. Ser., 2014)

(untitled) - Pomoni, K.; Sofianou, M.; Georgakopoulos, T.; Boukos, N.; Trapalis, C. (J. Alloys Compd., 2013)

(untitled) - Tian, J.; Zhao, Z.; Kumar, A.; Boughton, R. I.; Liu, H. (Chem. Soc. Rev., 2014)

(untitled) - Weng, Z.; Guo, H.; Liu, X.; Wu, S.; Yeung, K. W. K.; Chu, P. K. (RSC Adv., 2013)

(untitled) - Dette, C.; Pérez-Osorio, M. A.; Kley, C. S.; Punke, P.; Patrick, C. E.; Jacobson, P.; Giustino, F.; Jung, S. J.; Kern, K. (Nano Lett., 2014)

(untitled) - Reckers, P.; Dimamay, M.; Klett, J.; Trost, S.; Zilberberg, K.; Riedl, T.; Parkinson, B. A.; Brötz, J.; Jaegermann, W.; Mayer, T. (J. Phys. Chem. C, 2015)

(untitled) - Moerman, D.; Lazzaroni, R.; Douhéret, O. (Appl. Phys. Lett., 2011)

(untitled) - Weickert, J.; Auras, F.; Bein, T.; Schmidt-Mende, L. (J. Phys. Chem. C, 2011)

(untitled) - Huang, Y.-C.; Yen, W.-C.; Liao, Y.-C.; Yu, Y.-C.; Hsu, C.-C.; Ho, M.-L.; Chou, P.-T.; Su, W.-F. (Appl. Phys. Lett., 2010)

(untitled) - Wu, M.-C.; Wu, Y.-J.; Yen, W.-C.; Lo, H.-H.; Lin, C.-F.; Su, W.-F. (Nanoscale, 2010)

(untitled) - Zeng, T.-W.; Ho, C.-C.; Tu, Y.-C.; Tu, G.-Y.; Wang, L.-Y.; Su, W.-F. (Langmuir, 2011)

(untitled) - Phan, H.; Jahnke, J. P.; Chmelka, B. F.; Nguyen, T.-Q. (Appl. Phys. Lett., 2014)

(untitled) - Batra, Y.; Rai, D.; Mehta, B. R. (Appl. Phys. Express, 2013)

(untitled) - Zeng, T.-W.; Hsu, F.-C.; Tu, Y.-C.; Lin, T.-H.; Su, W.-F. (Chem. Phys. Lett., 2009)

(untitled) - Lin, Y.-Y.; Chu, T.-H.; Li, S.-S.; Chuang, C.-H.; Chang, C.-H.; Su, W.-F.; Chang, C.-P.; Chu, M.-W.; Chen, C.-W. (J. Am. Chem. Soc., 2009)

(untitled) - Dervaux, J.; Cormier, P.-A.; Konstantinidis, S.; Di Ciuccio, R.; Coulembier, O.; Dubois, P.; Snyders, R. (Vacuum, 2015)

(untitled) - Lasser, L.; Ronca, E.; Pastore, M.; De Angelis, F.; Cornil, J.; Lazzaroni, R.; Beljonne, D. (J. Phys. Chem. C, 2015)

(untitled) - Nüesch, F.; Carrara, M.; Zuppiroli, L. (Langmuir, 2003)

(untitled) - Krüger, J.; Bach, U.; Grätzel, M. (Adv. Mater., 2000)

(untitled) - Henning, A.; Günzburger, G.; Jöhr, R.; Rosenwaks, Y.; Bozic-Weber, B.; Housecroft, C. E.; Constable, E. C.; Meyer, E.; Glatzel, T. (Beilstein J. Nanotechnol., 2013)

(untitled) - Goh, C.; Scully, S. R.; McGehee, M. D. (J. Appl. Phys., 2007)

(untitled) - Wang, X.; Li, T.; Yu, R.; Yu, H.; Yu, J. (J. Mater. Chem. A, 2016)

(untitled) - Selçuk, S.; Selloni, A. (J. Phys. D: Appl. Phys., 2017)